2012
DOI: 10.1073/pnas.1201880109
|View full text |Cite
|
Sign up to set email alerts
|

From chemotaxis to the cognitive map: The function of olfaction

Abstract: A paradox of vertebrate brain evolution is the unexplained variability in the size of the olfactory bulb (OB), in contrast to other brain regions, which scale predictably with brain size. Such variability appears to be the result of selection for olfactory function, yet there is no obvious concordance that would predict the causal relationship between OB size and behavior. This discordance may derive from assuming the primary function of olfaction is odorant discrimination and acuity. If instead the primary fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
184
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(196 citation statements)
references
References 82 publications
(95 reference statements)
11
184
0
1
Order By: Relevance
“…In insects, mushroom bodies are known to be involved in contextual information processing, learning, and memory-including spatial memory (de Belle and Heisenberg, 1994;Heisenberg, 2003;Mizunami et al, 1998;Pascual and Preat, 2001;Zars et al, 2000). In fact, the size of arthropod mushroom bodies has recently been proposed to reflect the complexity of spatial navigation strategies (Jacobs, 2012). This "spatial orientation" hypothesis is consistent with our current knowledge of amblypygid neuroanatomy (i.e., large mushroom bodies) and their seemingly complex navigational capacities (present study).…”
Section: Discussionsupporting
confidence: 80%
“…In insects, mushroom bodies are known to be involved in contextual information processing, learning, and memory-including spatial memory (de Belle and Heisenberg, 1994;Heisenberg, 2003;Mizunami et al, 1998;Pascual and Preat, 2001;Zars et al, 2000). In fact, the size of arthropod mushroom bodies has recently been proposed to reflect the complexity of spatial navigation strategies (Jacobs, 2012). This "spatial orientation" hypothesis is consistent with our current knowledge of amblypygid neuroanatomy (i.e., large mushroom bodies) and their seemingly complex navigational capacities (present study).…”
Section: Discussionsupporting
confidence: 80%
“…The size of arthropod mushroom bodies has been hypothesized to reflect their spatial navigation strategies (Jacobs 2012), and amblypygids are well-known for their enlarged mushroom bodies (Strausfeld 1998). In the visually guided desert ant, Cataglyphis bicolor (Fabricius, 1793), researchers were able to demonstrate a remarkable increase in mushroom body size during the extremely short lifespan (ca.…”
Section: Environmental Interactionsmentioning
confidence: 99%
“…Horner also suggested that the enlarged olfactory lobes in T.rex were characteristic of scavengers (25). More recent studies (28,29) determined the olfactory lobes of modern birds are "poorly developed," inferring that enlarged olfactory lobes in T. rex are actually a secondary adaptation for predation navigation "to track mobile, dispersed prey" (30). T. rex has a calculated bite force stronger than that of any other terrestrial predator (7), between 35,000 and 57,000 Newtons (30,31), and possible ambulatory speeds between 20 and 40 kph (7,15,16), documenting that it had the capability to pursue and kill prey items.…”
mentioning
confidence: 99%